Rare case of giant unicystic ameloblastoma: Luminal variant. Issue 1 (2nd January 2018) - Kudva, Adarsh; Kamath, Abhay T.; Rao, Nirmala N.; Rajan, Jyotsna
Abstract: Objective and importance: Ameloblastoma is a locally aggressive benign tumor, commonly occurring in the mandible. While giant ameloblastoma of multicystic or plexiform variant have been reported, the authors report a rare case of giant unicystic ameloblastoma of luminal variant, which was treated by compartmental resection and planned for delayed reconstruction. Clinical presentation: A 46 year old male patient reported to the oral surgery out-patient department with a swelling of the left side mandible region of 2 years duration. He had undergone ayurvedic treatment for the same with no improvement. The size of the lesion on presenting was approximately 9 × 12 cm. Intervention: Compartmental resection with plan for secondary reconstruction, after adequate follow up period. Conclusion: While conservative management is being explored as a treatment option for unicystic ameloblastoma, resection is still the standard of care regardless of the histopathological subtype for giant lesions.